'The smell of the place': Managerialist culture in contemporary UK business schools. Issue 4 (7th August 2016) - De Vita, Glauco; Case, Peter
Abstract : By introducing an intentionally provocative critique of managerialist regimes which typify contemporary UK business school culture, we argue that current business school management practices generate a climate of mistrust and alienation amongst academics. Such a climate is not conducive to a reformative agenda that business schools should be pursuing if they are to improve staff morale and the educational environment. Drawing on Ghoshal's 'smell of the place' metaphor to structure this argument, we court deliberate irony and paradox. Rather than draw on heterodox theory to inform our critique we, instead, turn relatively mainstream management and organization theory against itself . Our argument is that even when examined through orthodox lenses, managerialist practices are found wanting and contradict the precepts of much mainstream normative theory.